Adhesive sheet, optical film with adhesive, and method for producing image display device

By using a combination of base polymer, photopolymerizable multifunctional compound, photopolymerization initiator and ultraviolet absorber in the adhesive sheet, the problem of photocuring of the adhesive sheet under fluorescent lamp is solved, and high transparency and high difference are achieved Absorption and improve adhesive reliability through ultraviolet curing.

CN112175540BActive Publication Date: 2024-12-27NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010504573.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-03
Filing Date
2020-06-05
Publication Date
2024-12-27
Estimated Expiration
2040-06-05

AI Technical Summary

Technical Problem

In the storage environment, existing adhesive sheets are prone to light curing due to fluorescent light, resulting in reduced transparency and insufficient adhesive reliability. The process of using ultraviolet absorbers is complicated and costly.

Method used

Optimized photocurable adhesives are prepared by adjusting the light transmittance and the type and amount of photopolymerization initiators using adhesive compositions containing base polymers, photopolymerizable multifunctional compounds, photopolymerization initiators and ultraviolet absorbers. The composite sheet ensures that light curing is not easy to cure under storage environment, and improves adhesive reliability through ultraviolet curing when needed.

Benefits of technology

It is achieved that light curing is not easy to occur in the storage environment, maintain high transparency and high-difference absorption, and perform sufficient light curing during excitation light irradiation, improving adhesive reliability and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112175540B_ABST
    Figure CN112175540B_ABST
Patent Text Reader

Abstract

The present invention relates to an adhesive sheet, an optical film with an adhesive, and a method for manufacturing an image display device. The present invention provides a photocurable adhesive sheet that can suppress photocuring caused by light such as fluorescent lamps in a storage environment and has excellent transparency. The adhesive sheet (5) contains: a base polymer having a cross-linked structure, a photopolymerizable multifunctional compound having two or more photopolymerizable functional groups in one molecule, a photopolymerization initiator, and an ultraviolet absorber. The transmittance of the adhesive sheet to light of a wavelength of 420 nm is 85% or more, the transmittance to light of a wavelength of 405 nm is 80% or more, and the transmittance to light of a wavelength of 380 nm is 4% to 25%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pressure-sensitive adhesive sheet and a pressure-sensitive adhesive optical film having the pressure-sensitive adhesive sheet. In addition, the present invention relates to a method for producing an image display device using the pressure-sensitive adhesive sheet. Background Art

[0002] Liquid crystal display devices and organic electroluminescent (EL) display devices are widely used as various image display devices such as mobile phones, smart phones, car navigation devices, monitors for personal computers, and televisions. In order to prevent damage to the image display panel caused by impact from the outer surface, a transparent front transparent plate such as a transparent resin plate or a glass plate (also called a "cover window", etc.) is sometimes provided on the visible side of the image display panel. In addition, devices having a touch panel on the visible side of the image display panel are becoming popular in recent years.

[0003] In an image display device in which a front transparent member such as a front transparent plate or a touch panel is arranged on the front of the image display panel, the image display panel and the front transparent member are bonded together via an adhesive sheet. Sometimes, a coloring layer (decorative printing layer) for the purpose of decoration or light shielding is formed on the periphery of the front transparent member. When an adhesive is bonded to a transparent member having a decorative printing layer, bubbles are easily generated around the printed height difference.

[0004] In order to solve such problems caused by the printing height difference of the front transparent member, a soft and thick adhesive sheet is usually used to impart printing height difference absorption. For example, Patent Document 1 shows the following example: an image display panel and a cover window with printing height difference are bonded together using a photocurable adhesive sheet containing a base polymer, a photopolymerizable multifunctional monomer, and a photopolymerization initiator. The photocurable adhesive is soft and has excellent height difference absorption before curing, and shows excellent bonding reliability after photocuring.

[0005] In a storage environment, a photocurable adhesive sheet may sometimes be photocured due to the effect of sunlight or light from a fluorescent lamp or the like. Once photocuring occurs, the adhesive becomes hard, so the height difference absorption is insufficient. Patent document 2 proposes the following scheme: a UV-absorbing release film is attached to the surface of the adhesive sheet to inhibit the photocuring of the adhesive sheet in a storage environment. In addition, patent document 2 states that by adding a UV absorber to the adhesive composition to make it UV-absorbing, it is possible to inhibit the degradation of components of an image display device such as an organic EL element and a polarizer caused by UV rays.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-227453

[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-173479 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In the manufacturing process of the adhesive sheet, the adhesive composition is sometimes photocured in a state where a release film is laminated. When ultraviolet rays are irradiated through a release film that absorbs ultraviolet rays, the light utilization efficiency is low and it is difficult to fully perform photocuring. Therefore, it is necessary to laminate a release film that does not absorb ultraviolet rays during photocuring, and replace and paste the release film that absorbs ultraviolet rays after photocuring, so the process becomes complicated and may also become the main reason for the increase in cost.

[0012] In the above-mentioned Patent Document 2, the photocuring inhibition caused by the ultraviolet absorber is suppressed by making the adhesive layer have ultraviolet absorbability and using a photopolymerization initiator having photosensitivity in the visible light region. However, when a photopolymerization initiator having high photosensitivity to visible light is used, the adhesive sheet is colored due to light absorption by the photopolymerization initiator, which is a major cause of reduced visibility of the image display device.

[0013] In view of the above circumstances, an object of the present invention is to provide a photocurable pressure-sensitive adhesive sheet which can suppress photocuring caused by light from a fluorescent lamp or the like in a storage environment and has excellent transparency.

[0014] Means used to solve problems

[0015] The adhesive sheet of the present invention is an adhesive sheet obtained by forming an adhesive composition containing a base polymer, a photopolymerizable multifunctional compound, a photopolymerization initiator and an ultraviolet absorber into a layer, and has photocurability. The transmittance of the adhesive sheet at a wavelength of 420nm is preferably 85% or more, the transmittance of the light at a wavelength of 405nm is preferably 80% or more, and the transmittance of the light at a wavelength of 380nm is preferably 4% to 25%. The transmittance of the adhesive sheet at a wavelength of 365nm is preferably 1% or less.

[0016] As the base polymer, for example, an acrylic polymer can be used. The base polymer preferably has a crosslinked structure. For example, the base polymer contains a hydroxyl-containing monomer as a monomer unit, and forms a crosslinked structure by bonding with the hydroxyl group through an isocyanate crosslinking agent.

[0017] The photopolymerizable multifunctional compound has two or more photopolymerizable functional groups in one molecule, and can use multifunctional (meth)acrylate, etc. The content of the photopolymerizable multifunctional compound in the adhesive composition constituting the adhesive sheet is, for example, about 0.3 to 10 parts by weight relative to 100 parts by weight of the base polymer.

[0018] The photopolymerization initiator is preferably one that has little absorption of visible light, and the extinction coefficient of the photopolymerization initiator at a wavelength of 405 nm is preferably 50 [mL·g -1 cm -1 The extinction coefficient of the photopolymerization initiator at a wavelength of 380 nm is preferably 80 [mL·g -1 cm -1 The photopolymerization initiator preferably has an absorption maximum in the wavelength range of 310 nm to 370 nm.

[0019] The adhesive composition constituting the adhesive sheet preferably contains 0.05 to 1 parts by weight of a photopolymerization initiator relative to 100 parts by weight of the base polymer. The content w (parts by weight) of the photopolymerization initiator relative to 100 parts by weight of the base polymer is related to the extinction coefficient ε (mL·g -1 cm -1 The product εw of the transmittance T (%) of the pressure-sensitive adhesive sheet at a wavelength of 380 nm and the above εw is preferably 10 to 1200.

[0020] As the ultraviolet absorber, triazine compounds, benzotriazole compounds, and the like can be preferably used.

[0021] The gel fraction of the adhesive sheet is preferably 30% to 80%. The adhesive sheet is preferably irradiated with 1000 mJ / cm 2 The gel fraction after light curing is more than 5% higher than that before light curing due to ultraviolet rays.

[0022] The adhesive sheet can be provided in the form of an adhesive sheet with a release film having release films temporarily attached to both sides. In addition, an optical film with an adhesive having the adhesive sheet laminated on one side of an optical film such as a polarizing plate can also be formed. The optical film with an adhesive can also be an optical film with an adhesive having adhesive sheets laminated on both sides of the optical film.

[0023] The adhesive sheet can be used to form an image display device having a transparent member with a height difference on the visible side surface. The adhesive sheet and the transparent member with the height difference are bonded together, and then the adhesive sheet is irradiated with active light to photocure the adhesive composition, thereby improving the bonding reliability.

[0024] Effects of the Invention

[0025] The adhesive in the adhesive sheet of the present invention is ultraviolet curing type. By using an ultraviolet curing type adhesive in laminating an image display panel with a front transparent plate, a touch panel or other front transparent member, the adhesive has high fluidity and high differential absorption during laminating, and by ultraviolet curing after laminating, the adhesive reliability is improved. By including an ultraviolet absorber in the adhesive composition, the photocuring reaction caused by light such as a fluorescent lamp in a storage environment can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a cross-sectional view showing a structural example of a pressure-sensitive adhesive sheet with a release film.

[0027] Figure 2 It is a cross-sectional view showing a structural example of an image display device.

[0028] Figure 3 It is a cross-sectional view showing an example of a laminated structure of an optical film with a pressure-sensitive adhesive.

[0029] Figure 4 It is a cross-sectional view showing an example of a laminated structure of an optical film with a pressure-sensitive adhesive.

[0030] Reference numerals

[0031] 5 Adhesive sheet

[0032] 1.2 Release film

[0033] 3 Polarizing plate

[0034] 4 Adhesive sheet

[0035] 6 Image display unit

[0036] 10 Image display panel

[0037] 7 Front transparent panel

[0038] 100 Image display device DETAILED DESCRIPTION

[0039] Figure 1 An adhesive sheet with release films 1 and 2 is shown, which are temporarily attached to both sides of an adhesive sheet 5. The adhesive sheet 5 is an adhesive sheet obtained by forming an adhesive composition containing a base polymer having a cross-linked structure, a photopolymerizable multifunctional compound, and a photopolymerization initiator into a layer, and has photocurability. The adhesive sheet preferably has high transparency. The total light transmittance of the adhesive sheet is preferably 85% or more, more preferably 90% or more. The haze of the adhesive sheet is preferably 1.5% or less, more preferably 1% or less.

[0040] There is no particular restriction on the thickness of the adhesive sheet, which can be set according to the type and shape of the adherend. In the case where a component with a printed height difference, such as a cover window to which decorative printing is implemented, is used as an adherend, the thickness of the adhesive sheet is preferably greater than the thickness of the printed height difference. The thickness of the adhesive sheet used for bonding with an adherend with a printed height difference, such as a cover window, is preferably 30 μm or more, more preferably 40 μm or more, and further preferably 50 μm or more. By increasing the thickness of the adhesive sheet, there is a tendency for the height difference absorbency to become higher. There is no particular restriction on the upper limit of the thickness of the adhesive sheet, but from the viewpoint of the productivity of the adhesive sheet, it is preferably 500 μm or less, more preferably 300 μm or less, and further preferably 250 μm or less.

[0041] The adhesive sheet may be a single layer or a multilayer structure obtained by laminating a plurality of adhesive layers. In the case where the adhesive sheet is a multilayer structure, at least one layer may be a photocurable adhesive composition containing an ultraviolet absorber. Alternatively, a plurality of adhesive layers may be a photocurable adhesive composition containing an ultraviolet absorber.

[0042] [Composition of adhesive]

[0043] The composition of the adhesive is not particularly limited, and an adhesive having a base polymer such as an acrylic polymer, a polysiloxane polymer, a polyester, a polyurethane, a polyamide, a polyvinyl ether, a vinyl acetate-vinyl chloride copolymer, a modified polyolefin, an epoxy, a fluorine-containing polymer, a natural rubber, a synthetic rubber, or other rubber-based polymer can be appropriately selected and used. In particular, an acrylic adhesive containing an acrylic base polymer having a cross-linked structure is preferably used from the viewpoint of excellent optical transparency, exhibiting appropriate adhesive properties such as wettability, cohesion, and tackiness, and excellent weather resistance, heat resistance, and the like.

[0044] <Base polymer>

[0045] The acrylic base polymer contains an alkyl (meth)acrylate as a main monomer component. In addition, in this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0046] As the alkyl (meth)acrylate, it is preferable to use an alkyl (meth)acrylate having an alkyl group with carbon atoms of 1 to 20. The alkyl group of the alkyl (meth)acrylate may have a branched chain, and the alkyl (meth)acrylate may have a cyclic alkyl group.

[0047] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, propylene (meth)acrylate, octyl ... Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, and the like.

[0048] Specific examples of the alkyl (meth)acrylate having an alicyclic alkyl group include: cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylates having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylates having an aliphatic hydrocarbon ring of three or more rings such as tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.

[0049] The amount of the alkyl (meth)acrylate is preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 60% by weight or more, relative to the total amount of the monomer components constituting the acrylic base polymer. From the viewpoint of adjusting the glass transition temperature (Tg) of the base polymer to an appropriate range, the amount of the alkyl (meth)acrylate having a linear alkyl group having 4 to 10 carbon atoms in the acrylic base polymer is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 45% by weight or more, relative to the total amount of the monomer components constituting the acrylic base polymer.

[0050] The acrylic base polymer preferably contains an acrylic monomer unit having a crosslinkable functional group as a copolymer component. The base polymer having a crosslinkable functional group allows the base polymer to react with a crosslinking agent to adjust the gel fraction of the pressure-sensitive adhesive to a desired range.

[0051] As acrylic monomers having cross-linkable functional groups, hydroxyl-containing monomers and carboxyl-containing monomers can be cited. For example, when an isocyanate cross-linking agent is used, a cross-linking structure is introduced by the reaction of a hydroxyl group with an isocyanate group. When an epoxy cross-linking agent is used, a cross-linking structure is introduced by the reaction of a carboxyl group with an epoxy group. Among them, it is preferred to use a hydroxyl-containing monomer as a copolymerization component of the base polymer and introduce a cross-linking structure by an isocyanate cross-linking agent. When the base polymer contains a hydroxyl-containing monomer as a monomer component, the cross-linking property of the base polymer is improved, and there is a tendency to suppress the white turbidity of the adhesive under a high temperature and high humidity environment, and an adhesive with high transparency can be obtained.

[0052] Examples of hydroxyl-containing monomers include (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (meth)acrylate (4-hydroxymethylcyclohexyl)methyl. Among them, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are preferred because they contribute greatly to the improvement of adhesive strength and can suppress white turbidity of the adhesive sheet under a high humidity environment.

[0053] The amount of the hydroxyl-containing monomer is preferably 3% to 40% by weight, more preferably 5% to 30% by weight, and further preferably 8% to 25% by weight relative to the total amount of monomer components constituting the acrylic base polymer. By increasing the amount of the hydroxyl-containing monomer, the unreacted functional groups of the crosslinking agent are reduced, so the gel fraction can be increased with a small amount of crosslinking, and the processability and height difference absorption of the adhesive sheet before photocuring can be taken into account.

[0054] Examples of the carboxyl group-containing monomer include acrylic monomers such as (meth)acrylic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid.

[0055] When the adhesive sheet is used for the bonding of the touch panel sensor, in order to prevent the corrosion of the electrode caused by the acid component, the acid content of the adhesive sheet is preferably low. The content of organic acid monomers such as (meth) acrylic acid in such an acid-free adhesive sheet is preferably 100 ppm or less, more preferably 70 ppm or less, and further preferably 50 ppm or less. The organic acid monomer content of the adhesive sheet is obtained by immersing the adhesive sheet in pure water, heating at 100°C for 45 minutes, and quantifying the acid monomers extracted into the water using an ion chromatograph.

[0056] In order to reduce the acid monomer content in the adhesive sheet, the amount of organic acid monomer components such as (methyl) acrylic acid in the monomer component of the acrylic base polymer is preferably few. Therefore, in order to make the adhesive sheet acid-free, preferably the base polymer does not contain organic acid monomer (carboxyl-containing monomer) as monomer component in fact. In the acid-free adhesive sheet, relative to 100 weight parts of the monomer component of the base polymer, the amount of carboxyl-containing monomer is preferably below 0.5 weight part, more preferably below 0.1 weight part, further preferably below 0.05 weight part, ideally 0.

[0057] The acrylic base polymer may contain a nitrogen-containing monomer as a constituent monomer component. Examples of the nitrogen-containing monomer include N-vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl Vinyl monomers such as oxazole, vinyl morpholine, (meth) acryloyl morpholine, N-vinyl carboxylic acid amides, and N-vinyl caprolactam; cyano group-containing monomers such as acrylonitrile and methacrylonitrile, etc. Among them, N-vinyl pyrrolidone is preferred because of its high effect of improving the adhesive force due to the improvement of the cohesive force.

[0058] The acrylic base polymer contains high polar monomers such as hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers as monomer components, which tends to improve the cohesive force of the adhesive and the adhesive retention. The amount of the high polar monomer (the total of the hydroxyl-containing monomers, carboxyl-containing monomers, and nitrogen-containing monomers) is preferably 10% to 60% by weight, more preferably 15% to 50% by weight, and further preferably 18% to 40% by weight, relative to the total amount of monomer components constituting the acrylic base polymer. In addition, the amount of the nitrogen-containing monomer is preferably 3% to 25% by weight, more preferably 5% to 20% by weight, and further preferably 7% to 15% by weight, relative to the total amount of monomer components constituting the acrylic base polymer.

[0059] As monomer components other than the above, the acrylic base polymer may include anhydride group-containing monomers, caprolactone adducts of (meth)acrylic acid, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, vinyl acetate, vinyl propionate, styrene, α-methylstyrene and other vinyl monomers; acrylonitrile, methacrylonitrile and other cyano group-containing monomers; glycidyl (meth)acrylate and other epoxy group-containing monomers; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate and other glycol (meth)acrylate monomers; tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, polysiloxane (meth)acrylate, 2-methoxyethyl (meth)acrylate and other (meth)acrylate monomers; and the like.

[0060] The acrylic base polymer is obtained by polymerizing the above-mentioned monomer components by various known methods such as solution polymerization, emulsion polymerization, and bulk polymerization. From the viewpoints of the balance of characteristics such as the adhesive force and holding power of the adhesive, cost, etc., as a polymerization method, solution polymerization is preferred. As a solvent for solution polymerization, ethyl acetate, toluene, etc. are generally used. The solution concentration is generally about 20% by weight to about 80% by weight. As a polymerization initiator, azo initiators, peroxide initiators, redox initiators obtained by combining peroxides with reducing agents (for example, a combination of persulfates and sodium bisulfite, a combination of peroxides and sodium ascorbate) and other thermal polymerization initiators can be preferably used. The amount of the polymerization initiator used is not particularly limited, for example, relative to 100 parts by weight of the total amount of the monomer components forming the base polymer, preferably about 0.005 parts by weight to about 5 parts by weight, more preferably about 0.02 parts by weight to about 3 parts by weight.

[0061] In order to adjust the molecular weight of the base polymer, a chain transfer agent may be used. As the chain transfer agent, for example, mercaptans such as α-thioglycerol, dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol can be preferably used.

[0062] The viscoelasticity of the adhesive sheet before photocuring is easily affected by the constituent components and molecular weight of the base polymer. The weight average molecular weight of the acrylic base polymer is preferably 100,000 to 2,000,000, more preferably 150,000 to 1,000,000, and further preferably 200,000 to 700,000. It should be noted that the molecular weight of the base polymer refers to the molecular weight before the cross-linking structure is introduced.

[0063] <Cross-linking structure of base polymer>

[0064] Methods for introducing a cross-linked structure into a base polymer generally include: (1) a method of polymerizing a base polymer having a functional group capable of reacting with a cross-linking agent, then adding a cross-linking agent and reacting the base polymer with the cross-linking agent; and (2) a method of introducing a branched structure (cross-linked structure) into a polymer chain by including a photopolymerizable polyfunctional compound in the polymerization components of the base polymer; etc.

[0065] The base polymer of the adhesive sheet of the present invention has a cross-linked structure introduced by the method of (1) above. In addition, the adhesive composition constituting the adhesive sheet contains a photopolymerizable multifunctional compound, and is photocured after the adhesive sheet is attached to the adherend, thereby introducing the cross-linked structure of (2) above. That is, before photocuring, the base polymer of the adhesive sheet of the present invention has a cross-linked structure formed by a (thermal) cross-linking agent such as an isocyanate cross-linking agent. In the adhesive sheet after photocuring, in addition to the cross-linked structure formed by an isocyanate cross-linking agent, a cross-linked structure formed by a photopolymerizable multifunctional compound (photocross-linking agent) such as a multifunctional (meth) acrylate is also introduced.

[0066] <Cross-linking agent>

[0067] A crosslinking structure is introduced into the base polymer by adding a crosslinking agent after polymerization and heating as needed. In order to distinguish the crosslinking structure introduced by a photopolymerizable multifunctional compound, crosslinking using an isocyanate crosslinking agent is sometimes described as "thermal crosslinking", but the introduction of the crosslinking structure using a crosslinking agent may not be accompanied by heating. By introducing a thermal crosslinking structure into the acrylic base polymer, the processability and processing dimensional stability of the adhesive sheet before photocuring can be improved.

[0068] Examples of the crosslinking agent include compounds that react with functional groups such as hydroxyl groups and carboxyl groups contained in the base polymer. Specific examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, metal chelate crosslinking agents, etc.

[0069] Among them, isocyanate crosslinking agents and epoxy crosslinking agents are preferred because of their high reactivity with the hydroxyl and carboxyl groups of the base polymer and the ease of introducing a crosslinked structure. These crosslinking agents react with functional groups such as hydroxyl and carboxyl groups introduced into the base polymer to form a crosslinked structure. For acid-free adhesives in which the base polymer does not contain a carboxyl group, it is preferred to use an isocyanate crosslinking agent and form a crosslinked structure through the reaction of the hydroxyl group in the base polymer with the isocyanate crosslinking agent.

[0070] As the isocyanate crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule can be used. Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (e.g., "Coronate L" manufactured by Tosoh Corporation), trimethylolpropane / hexamethylene diisocyanate trimer adduct (e.g., "Coronate HL" manufactured by Tosoh Corporation), trimethylolpropane adduct of xylylene diisocyanate (e.g., "Takenate D110N" manufactured by Mitsui Chemicals, Inc.), isocyanurate form of hexamethylene diisocyanate (e.g., "Coronate 100N" manufactured by Tosoh Corporation), and isocyanurate form of hexamethylene diisocyanate (e.g., "Coronate 100N" manufactured by Tosoh Corporation). HX") and other isocyanate adducts.

[0071] By adjusting the amount of crosslinking agent added, the gel fraction of the adhesive sheet can be adjusted to within a specified range. The amount of crosslinking agent added is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.8 parts by weight, further preferably 0.05 to 0.5 parts by weight, and particularly preferably 0.08 to 0.3 parts by weight relative to 100 parts by weight of the base polymer. The more the amount of crosslinking agent added, the higher the gel fraction of the adhesive sheet before photocuring tends to be.

[0072] <Photopolymerizable multifunctional compound>

[0073] The photopolymerizable multifunctional compound contained in the adhesive sheet has two or more photopolymerizable functional groups in one molecule. The photopolymerizable functional group can be any one of a free radical polymerizable functional group, a cation polymerizable functional group, and an anion polymerizable functional group, but from the aspect of excellent reactivity, a free radical polymerizable functional group with an unsaturated double bond (ethylenically unsaturated group) is preferred. As the photopolymerizable multifunctional compound, from the aspect of high compatibility with acrylic base polymers, multifunctional (meth) acrylates are preferred, and from the aspect of high photoradical reactivity, multifunctional acrylates are particularly preferred.

[0074] Examples of the multifunctional (meth)acrylate include hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, bisphenol A ethylene oxide-modified di(meth)acrylate, bisphenol A propylene oxide-modified di(meth)acrylate, alkanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, pentaerythritol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and glycerol di(meth)acrylate. difunctional (meth)acrylates such as di(meth)acrylate, di(meth)acrylate, and di(meth)acrylate; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; tetrafunctional (meth)acrylates such as di(trimethylolpropane) tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate; pentafunctional or higher (meth)acrylates such as dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate.

[0075] The content of the photopolymerizable multifunctional compound in the photocurable adhesive sheet is preferably 0.3 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, relative to 100 parts by weight of the base polymer. The greater the content of the multifunctional compound, the greater the gel fraction of the adhesive after photocuring and the higher the adhesive reliability. On the other hand, when the content of the multifunctional compound is too large, the adhesive sometimes becomes too hard, and the impact resistance and adhesive retention at low temperatures are reduced. Relative to 100 parts by weight of the base polymer, the amount of the photopolymerizable multifunctional compound can be more than 0.7 parts by weight or more than 1 part by weight, and can be less than 4 parts by weight or less than 3 parts by weight.

[0076] <Photopolymerization initiator>

[0077] The photocurable adhesive composition contains a photopolymerization initiator. The photopolymerization initiator generates free radicals, acids, bases, etc. by irradiation with active light such as ultraviolet rays, and can be appropriately selected according to the type of photopolymerizable compound. When a multifunctional (meth)acrylate is used as the photopolymerizable compound, it is preferred to use a photoradical polymerization initiator as the photopolymerization initiator.

[0078] As the photo-radical polymerization initiator, a photo-radical polymerization initiator having sensitivity to ultraviolet rays having a wavelength shorter than 405 nm is preferred, and examples thereof include hydroxy ketones, benzyl dimethyl ketals, amino ketones, acyl phosphine oxides, benzophenones, trichloromethyl-containing triazine derivatives, etc. The photo-radical polymerization initiator may be used alone or in combination of two or more.

[0079] The photopolymerization initiator preferably has low sensitivity to light having a wavelength longer than 400 nm (visible light). The extinction coefficient ε of the photopolymerization initiator at a wavelength of 405 nm is preferably 50 [mL·g -1 cm -1 ] or less, more preferably 20 [mL·g -1 cm -1 ] or less, more preferably 10 [mL·g -1 cm -1 ] or less. By using a photopolymerization initiator with little absorption of light of wavelength 405nm, the transparency of the adhesive sheet can be improved. In addition, if a photopolymerization initiator with low sensitivity to visible light is used, the photopolymerization of the adhesive caused by external light in the storage environment is not easy to proceed, so the storage stability of the adhesive sheet can be improved. The extinction coefficient of the photopolymerization initiator is a value calculated from the absorbance of a 0.001g / mL acetonitrile solution measured by a UV-visible spectrophotometer using a quartz cell with an optical path length of 1cm.

[0080] From the viewpoint of improving the storage stability of the adhesive sheet, it is preferred to use a photo-radical polymerization initiator that does not show an absorption maximum at a wavelength longer than 380nm. A photo-radical polymerization initiator that shows an absorption maximum at a wavelength longer than 380nm easily absorbs light from a fluorescent lamp (mainly a mercury bright line of 405nm) to generate photo-radicals. If the maximum wavelength of light absorption of the photo-radical polymerization initiator is below 370nm, the amount of free radicals generated by light under a storage environment such as a fluorescent lamp is small. Therefore, even when the adhesive sheet is stored for a long time under a fluorescent lamp, a high effective concentration of the photo-radical polymerization initiator can be maintained.

[0081] In order to make the storage stability high and to improve the adhesion reliability with the adherend by light irradiation even after long-term storage, the maximum wavelength of light absorption of the photopolymerization initiator contained in the adhesive sheet is preferably below 370nm. On the other hand, in order to improve the photocuring efficiency based on ultraviolet irradiation, it is preferred that the photopolymerization initiator has a light absorption maximum at a wavelength longer than 310nm. In summary, in order to take into account the transparency and storage stability of the adhesive sheet, the photopolymerization initiator contained in the adhesive sheet preferably does not have an absorption maximum at a wavelength longer than 380nm, and has an absorption maximum in the range of wavelengths of 310nm to 370nm. The photopolymerization initiator more preferably has an absorption maximum in the range of wavelengths of 310nm to 355nm. The absorption maximum wavelength of the photopolymerization initiator is further preferably 315nm to 350nm, and particularly preferably 320nm to 345nm.

[0082] The photopolymerization initiator preferably has sensitivity to light with a wavelength of 380 nm. By having sensitivity to light with a wavelength of 380 nm, even when the adhesive sheet contains an ultraviolet absorber, the photopolymerization initiator can absorb light that is not absorbed by the ultraviolet absorber, thereby enabling appropriate photocuring. The extinction coefficient of the photopolymerization initiator at a wavelength of 380 nm is preferably 80 [mL·g -1 cm -1 ] or more, more preferably 100 [mL·g -1 cm -1 ] or more, more preferably 120 [mL·g -1 cm -1 The extinction coefficient of the photopolymerization initiator at a wavelength of 380 nm is usually 1000 [mL·g -1 cm -1 ] or less, and may be 500 [mL·g -1 cm -1 ] or less than 300[mL·g -1 cm -1 ]the following.

[0083] The content of the photopolymerization initiator in the pressure-sensitive adhesive sheet may be set based on absorbance or the like. The extinction coefficient ε (mL·g -1 cm -1 The product εw of ) and the content w (parts by weight) of the photopolymerization initiator relative to 100 parts by weight of the base polymer is preferably 10 to 100, more preferably 15 to 80. The larger εw is, the easier it is to perform photocuring, but on the other hand, photocuring caused by light from a fluorescent lamp in a storage environment is also easier to perform.

[0084] If εw is within the above range, photocuring of the adhesive in a storage environment is suppressed, and sufficient photoreactivity is exhibited when irradiated with light for photocuring. The product εw of the extinction coefficient ε of the photopolymerization initiator and the content w may be 20 or more, 25 or more, or 30 or more. εw may be 60 or less, or 50 or less. The content w of the photopolymerization initiator relative to 100 parts by weight of the base polymer is, for example, 0.05 to 1 part by weight, preferably 0.08 to 0.5 parts by weight.

[0085] <Ultraviolet light absorber>

[0086] The ultraviolet absorber has the function of inhibiting the photocuring reaction of the adhesive sheet under the storage environment. In a composition containing an ultraviolet absorber in addition to a photopolymerization initiator, even when light of a wavelength to which the photopolymerization initiator has photosensitivity is irradiated from a fluorescent lamp or the like, the amount of light absorbed by the polymerization initiator becomes relatively small because the amount of light absorbed by the ultraviolet absorber is large. Therefore, the photocuring (polymerization reaction of a photopolymerizable multifunctional compound) caused by light from a fluorescent lamp or the like under the storage environment of the adhesive sheet can be inhibited.

[0087] Examples of the ultraviolet absorber include benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, triazine ultraviolet absorbers, salicylate ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers. Triazine ultraviolet absorbers and benzotriazole ultraviolet absorbers are preferred because they have high absorption of ultraviolet rays in the wavelength range of 320 nm to 370 nm and excellent compatibility with acrylic base polymers. Among them, triazine ultraviolet absorbers containing a hydroxyl group (particularly hydroxyphenyltriazine ultraviolet absorbers) and benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule are particularly preferred.

[0088] As the ultraviolet absorber, a commercially available product can be used. Commercially available products of triazine-based ultraviolet absorbers include 2-[4-[(2-hydroxy-3-(alkoxy)propoxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (manufactured by BASF, “TINUVIN 400”), a reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine and glycidyl acid (2-ethylhexyl) ester (manufactured by BASF, “TINUVIN 405”), (2,4-bis[2-hydroxy-4-butoxyphenyl]-6(2,4-dibutoxyphenyl)-1,3,5-triazine (manufactured by BASF, “TINUVIN 460”), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)-phenol (manufactured by BASF, “TINUVIN 405”). 577”), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (manufactured by BASF, “TINUVIN 479”), bis-ethylhexyloxyphenol methoxyphenyl triazine (manufactured by BASF, “Tinosorb S”), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol (manufactured by ADEKA, “ADK STAB LA-46”), etc.

[0089] Examples of commercially available benzotriazole ultraviolet absorbers include 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF, "TINUVIN 928"), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (manufactured by BASF, "TINUVIN PS"), 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (manufactured by BASF, "TINUVIN 900"), 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF, "TINUVIN 928”), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (manufactured by BASF, “TINUVIN 571”), 2-(2H-benzotriazol-2-yl)-p-cresol (manufactured by BASF, “TINUVIN P”), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (manufactured by BASF, “TINUVIN 234”), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (manufactured by BASF, “TINUVIN 326”), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol (manufactured by BASF, “TINUVIN 328”), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (manufactured by BASF, “TINUVIN 329”), ester compound of phenylpropionic acid and 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy (C7-C9 side chain and linear alkyl) (manufactured by BASF, “TINUVIN 384-2”), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propanoate and polyethylene glycol (manufactured by BASF, “TINUVIN 1130”), reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl) propionate and polyethylene glycol 300 (manufactured by BASF, “TINUVIN213”), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole (manufactured by Sumitomo Chemical Co., Ltd., “Sumisorb 250”), etc.

[0090] The content of the ultraviolet light absorber in the adhesive sheet is, for example, about 0.05 to about 3 parts by weight, preferably about 0.1 to about 1 part by weight, relative to 100 parts by weight of the base polymer. The more the amount of ultraviolet light absorber, the more it tends to suppress the photocuring of the adhesive sheet caused by light from fluorescent lamps, etc. in the storage environment. On the other hand, when the amount of ultraviolet light absorber is too much, even if excitation light (ultraviolet light) is irradiated for photocuring, most of the excitation light is absorbed by the ultraviolet light absorber, and the amount of light absorbed by the photopolymerization initiator becomes small, so sometimes the curing is insufficient.

[0091] (Oligomer)

[0092] The adhesive composition may contain various oligomers in order to adjust the adhesive force of the adhesive sheet, adjust the viscosity, etc. As the oligomer, for example, an oligomer having a weight average molecular weight of about 1000 to about 30000 may be used. As the oligomer, acrylic oligomers are preferred from the aspect of excellent compatibility with acrylic base polymers.

[0093] (Silane coupling agent)

[0094] In order to adjust the adhesive force, a silane coupling agent may be added to the adhesive composition. When a silane coupling agent is added to the adhesive composition, the amount of the silane coupling agent added is generally about 0.01 to 5.0 parts by weight, preferably about 0.03 to 2.0 parts by weight, relative to 100 parts by weight of the base polymer.

[0095] (Other additives)

[0096] In addition to the above-exemplified components, the pressure-sensitive adhesive composition may further contain additives such as a chain transfer agent, a tackifier, a plasticizer, a softener, an anti-degradation agent, a filler, a colorant, an antioxidant, a surfactant, and an antistatic agent.

[0097] [Formation of Adhesive Sheet]

[0098] The adhesive composition is prepared by mixing a crosslinking agent, a photopolymerizable multifunctional compound, a photopolymerization initiator, an ultraviolet absorber, and additives such as oligomers and silane coupling agents as required in a base polymer. The adhesive composition preferably has a viscosity suitable for coating on a substrate (for example, about 0.5 Pa·second to about 20 Pa·second). The viscosity of the adhesive composition can be adjusted to an appropriate range by adjusting the molecular weight of the base polymer, the amount of the photopolymerizable multifunctional compound, the composition, molecular weight, and amount of other components (such as oligomers). In order to adjust the viscosity, etc., a thickening additive can be used.

[0099] Adhesive composition is applied on substrate and solvent is dried and removed as required, thus forming adhesive sheet on substrate. As the substrate used in the formation of adhesive sheet, any appropriate substrate can be used. Substrate can also be a release film with a release layer on the contact surface with adhesive sheet.

[0100] As the film substrate of the release film, a film containing various resin materials can be used. As the resin material, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, polyphenylene sulfide resins, etc. can be listed. Among them, polyester resins such as polyethylene terephthalate are particularly preferred. The thickness of the film substrate is preferably 10μm to 200μm, more preferably 25μm to 150μm. As the material of the release layer, polysiloxane release agents, fluorine-containing release agents, long-chain alkyl release agents, fatty acid amide release agents, etc. can be listed. The thickness of the release layer is usually about 10nm to about 2000nm.

[0101] As a coating method for applying the adhesive composition to a substrate, various methods can be used, such as roll coating, contact roll coating, gravure coating, reverse coating, roller brushing, spraying, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, die lip coating, and die coating.

[0102] When the adhesive composition contains a solvent, after the adhesive composition is applied to the substrate, the solvent is preferably dried. As a drying method, a suitable method can be appropriately adopted according to the purpose. The heating drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. The drying time can be appropriately adopted for a suitable time. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.

[0103] After the solvent is dried, a cover sheet is preferably provided to protect the surface of the adhesive sheet. As the cover sheet, a release film having a release layer on the surface in contact with the adhesive sheet is preferably used, similarly to the base film.

[0104] After applying the adhesive composition on the substrate, heating is performed as needed to introduce a cross-linked structure into the base polymer. The heating temperature and heating time can be appropriately set according to the type of cross-linking agent used. Generally, the heating temperature is in the range of 20°C to 160°C and the heating time is about 1 minute to about 7 days. The heating for drying the solvent can also serve as the heating for cross-linking. As mentioned above, the introduction of the cross-linked structure does not need to be accompanied by heating.

[0105] In order to promote the formation of the cross-linked structure, a cross-linking catalyst can be used. For example, as a cross-linking catalyst for an isocyanate cross-linking agent, there can be cited: tetra-n-butyl titanate, tetraisopropyl titanate, ferric acetylacetonate, butyl tin oxide, dioctyltin dilaurate, dibutyltin dilaurate and other metal cross-linking catalysts (especially tin-containing cross-linking catalysts) and the like.

[0106] By laminating the release films 1 and 2 on the surface of the adhesive sheet 5, a Figure 1 The adhesive sheet shown here has release films temporarily attached to both sides. The base material or cover sheet used to form the adhesive sheet may be used directly as the release films 1 and 2.

[0107] When release films 1 and 2 are provided on both sides of the adhesive sheet 5, the thickness of the release film 1 on one side may be the same as or different from the thickness of the release film 2 on the other side. The peeling force when peeling off the release film temporarily attached to one side from the adhesive sheet 5 may be the same as or different from the peeling force when peeling off the release film temporarily attached to the other side from the adhesive sheet 5. In the case where the peeling forces of the two are different, the workability is excellent when the release film 2 (light release film) with relatively small peeling force is first peeled off from the adhesive sheet 5 and attached to the first adherend, and then the release film 1 (heavy release film) with relatively large peeling force is peeled off and attached to the second adherend.

[0108] [Physical properties of adhesive sheet]

[0109] By introducing a cross-linked structure formed by an isocyanate cross-linking agent into the base polymer, the gel fraction is increased. The gel fraction of the adhesive sheet before photocuring is preferably 30% to 80%. If the gel fraction is 80% or less, the adhesive can easily follow the printed height difference of the cover window, etc., and can suppress the gap near the height difference. In addition, if the gel fraction is 30% or more, the operability and processability of the adhesive sheet are excellent. The gel fraction of the adhesive sheet before photocuring is more preferably 35% to 70%, and more preferably 40% to 65%.

[0110] The gel fraction of the adhesive sheet can be obtained as the content of insoluble components in solvents such as ethyl acetate. Specifically, it is obtained as the weight fraction (unit: weight %) of the insoluble components after the adhesive constituting the adhesive sheet is immersed in ethyl acetate at 23°C for 7 days relative to the sample before immersion. Generally, the gel fraction of a polymer is equal to the degree of crosslinking. The more crosslinked parts in the polymer, the greater the gel fraction. The gel fraction (the amount of crosslinked structure introduced) can be adjusted to the desired range by the method of introducing the crosslinked structure, the type and amount of the crosslinking agent, etc.

[0111] When the photocurable adhesive sheet is irradiated with active light such as ultraviolet rays and photocured, the gel fraction of the adhesive sheet is increased by photopolymerization of the photocurable multifunctional compound, and the adhesive reliability to the adherend is improved. 2 The gel fraction of the adhesive sheet after light curing by ultraviolet light is preferably 40% or more, more preferably 50% or more. The gel fraction of the adhesive sheet after light curing may be 55% or more or 60% or more. The gel fraction of the adhesive sheet after light curing may be 100% or less, 95% or less, or 90% or less.

[0112] By irradiating 1000mJ / cm 2 The gel fraction of the adhesive sheet after photocuring by ultraviolet light is preferably 5% or more greater than the gel fraction of the adhesive sheet before photocuring. When the gel fraction is increased by 5% or more, there is a tendency for the adhesive reliability to be improved.

[0113] After the adhesive sheet was left to stand under a fluorescent lamp for 7 days, it was irradiated with 1000 mJ / cm 2 In the case of light curing by ultraviolet light, the gel fraction after light curing is preferably 5% or more greater than the gel fraction of the adhesive sheet after standing under a fluorescent lamp and before light curing. As described later, by appropriately selecting and adjusting the type and amount of the photopolymerization initiator and the ultraviolet absorber, light curing under a fluorescent lamp is not easy to proceed, and light curing is appropriately performed when irradiating the excitation light (ultraviolet light) for curing, so that the difference in gel fraction before and after light curing can be adjusted to 5% or more.

[0114] Since the adhesive sheet of the present invention contains a photopolymerization initiator and an ultraviolet absorber, the adhesive sheet is not easily photocured by light from a fluorescent lamp or the like in a storage environment. The intensity of light in a storage environment such as light from a fluorescent lamp is sufficiently small compared to the excitation light when the adhesive sheet is photocured, so even if the adhesive sheet is placed under a fluorescent lamp for a short time, the photocuring reaction hardly proceeds. However, when the adhesive sheet is stored for a long time under a fluorescent lamp, the cumulative amount of light-excited components (such as photo radicals) generated by the photopolymerization initiator that absorbs the light from the fluorescent lamp becomes larger, and its influence cannot be ignored sometimes. Specifically, due to the photo radicals generated by the photopolymerization initiator, the photopolymerization of the photopolymerizable multifunctional compound proceeds, the gel fraction of the adhesive increases, and the adhesive becomes hard, so that the height difference absorption is sometimes reduced.

[0115] In the adhesive sheet of the present invention, the photocurable adhesive composition constituting the adhesive sheet further comprises, in addition to the base polymer, the photocuring agent and the photopolymerization initiator, an ultraviolet absorber, comprising an ultraviolet absorber that absorbs light (ultraviolet light) in a wavelength region overlapping with the light absorption band (excitation wavelength) of the photopolymerization initiator. By adjusting the type and / or addition amount of the ultraviolet absorber according to the type (light absorption characteristics) of the photopolymerization initiator, the transmittance of light in the wavelength range in which the photopolymerization initiator has photosensitivity can be maintained, and the photocuring of the adhesive sheet caused by light from a fluorescent lamp or the like can be suppressed.

[0116] A general fluorescent lamp emits a mercury bright line with a wavelength of 365nm. Therefore, if the transmittance of the light with a wavelength of 365nm of the adhesive sheet is reduced by adding an ultraviolet absorber, the photocuring of the adhesive sheet in the storage environment can be suppressed even when the adhesive sheet is stored for a long time under a fluorescent lamp. From the viewpoint of suppressing the photocuring of the adhesive sheet in the storage environment, the transmittance of the light with a wavelength of 365nm of the adhesive sheet is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.3% or less. The transmittance of the light with a wavelength of 365nm of the adhesive sheet may be 0.2% or less or 0.1% or less.

[0117] From the viewpoint of improving visible light transparency, the transmittance of the adhesive sheet at a wavelength of 420 nm is preferably 85% or more, more preferably 88% or more. The transmittance of the adhesive sheet at a wavelength of 405 nm is preferably 80% or more, more preferably 83% or more. As described above, since the light sensitivity of the photopolymerization initiator at a wavelength of 405 nm is small (or has no sensitivity), even when the transmittance of the adhesive sheet at a wavelength of 405 nm is large, photocuring of the adhesive sheet caused by external light, fluorescent light, etc. in a storage environment hardly occurs.

[0118] As described above, the transmittance of the light of wavelength 365nm of the adhesive sheet is low, and most of the light near wavelength 365nm is absorbed by the ultraviolet absorber. In addition, the light of wavelength 405nm of the photopolymerization initiator is small in sensitivity (or has no sensitivity). Therefore, even if the adhesive sheet is irradiated with light of wavelength 365nm and / or light of wavelength 405nm, the light that can be used by the photopolymerization initiator is very small, and photocuring is hardly performed.

[0119] By adjusting the light transmittance of the adhesive sheet so that the photopolymerization initiator can effectively absorb light in a wavelength range longer than 365nm and shorter than 405nm, photocuring is not easy to proceed in a storage environment, and photocuring can be properly performed when irradiated with excitation light. Specifically, it is preferred that the photopolymerization initiator contained in the adhesive sheet can effectively utilize light near a wavelength of 380nm. Therefore, the transmittance of the light of a wavelength of 380nm of the adhesive sheet is preferably 4% or more, and more preferably 5% or more.

[0120] The greater the transmittance of light with a wavelength of 380nm, the higher the curing efficiency when the adhesive sheet is photocured by irradiating the excitation light. On the other hand, when the transmittance of light with a wavelength of 380nm is too large, the photocuring of the adhesive sheet sometimes proceeds due to the external light in the storage environment, and the height difference absorption decreases. In addition, when it is made to have ultraviolet absorptivity by adding an ultraviolet absorber, when the transmittance of light with a wavelength of 380nm is large, the transmittance of light with a wavelength of 365nm also tends to increase, and sometimes it is not possible to fully suppress the photocuring of the adhesive sheet caused by light such as fluorescent lamps in the storage environment. Therefore, the transmittance of light with a wavelength of 380nm of the adhesive sheet is preferably 25% or less, and more preferably 20% or less.

[0121] When observing the light transmission spectrum of the adhesive sheet from the short wavelength side to the long wavelength side, the wavelength at which the transmittance reaches 10% or more (hereinafter sometimes referred to as "10% cut-off wavelength") is preferably in the range of 370nm to 385nm. If the amount of ultraviolet absorber added is increased, the 10% cut-off wavelength moves to the short wavelength side, and if the amount of ultraviolet absorber added is reduced, the 10% cut-off wavelength moves to the long wavelength side.

[0122] From the viewpoint of suppressing the photocuring of the adhesive sheet in a storage environment and improving the photocuring efficiency when irradiating the excitation light, it is preferred that in addition to adjusting the light absorption characteristics of the adhesive sheet by adding an ultraviolet absorber as described above, the amount of photopolymerization initiator added is adjusted according to the light transmittance of the adhesive sheet. Considering the transmittance T (%) of the light of a wavelength of 380nm of the adhesive sheet, when T is large, the amount of light that can be absorbed by the photopolymerization initiator is large even when the amount of the photopolymerization initiator is small, so that the photocuring efficiency when irradiating the excitation light can be ensured. On the other hand, when T is small, even if the amount of the photopolymerization initiator is increased, photocuring caused by light such as a fluorescent lamp in a storage environment is not likely to occur.

[0123] Therefore, when the transmittance T of the adhesive sheet for light of wavelength 380 nm is small, it is preferred to relatively increase the amount of the photopolymerization initiator, and when T is large, it is preferred to relatively reduce the amount of the photopolymerization initiator. As described above, the effective amount of the photopolymerization initiator in the adhesive sheet can be evaluated by the product εw of the content of the photopolymerization initiator and the extinction coefficient ε.

[0124] From the viewpoint of suppressing the photocuring of the adhesive sheet in the storage environment and improving the photocuring efficiency when irradiated with excitation light, it is preferred that the transmittance T (%) of the adhesive sheet at a wavelength of 380 nm is proportional to the content w (parts by weight) of the photopolymerization initiator relative to 100 parts by weight of the base polymer and the extinction coefficient ε (mL·g) of the photopolymerization initiator at a wavelength of 380 nm. -1 cm -1 ) is within the specified range.

[0125] The εwT of the adhesive sheet is preferably 100 to 1200, more preferably 110 to 1000. εwT may be 120 or more, 130 or more, 140 or more, or 150 or more. εwT may be 700 or less, 600 or less, or 500 or less. The larger the εwT, the more the photocuring efficiency when irradiated with excitation light tends to be improved, and the smaller the εwT, the more the photocuring of the adhesive sheet in the storage environment tends to be suppressed.

[0126] [Image display device]

[0127] The adhesive sheet of the present invention can be used for laminating various transparent components and opaque components. The type of adherend is not particularly limited, and various resin materials, glass, metal, etc. can be cited. The adhesive sheet of the present invention is suitable for laminating optical components of image display devices due to its high transparency. In particular, the adhesive sheet of the present invention is suitable for laminating transparent components such as a front transparent plate and a touch panel on the visible side surface of an image display device due to its excellent height difference absorption and impact resistance.

[0128] Figure 21 is a cross-sectional view showing an example of a stacked structure of an image display device in which a front transparent plate 7 is bonded to a visible side surface of an image display panel 10 via an adhesive sheet 5. The image display panel 10 has a polarizing plate 3, which is bonded to a visible side surface of an image display unit 6 such as a liquid crystal unit or an organic EL unit via an adhesive sheet 4. The front transparent plate 7 is provided with a printed layer 76 on the periphery of one surface of a transparent flat plate 71. For example, a transparent resin plate such as an acrylic resin or a polycarbonate resin or a glass plate can be used for the transparent flat plate 71. The transparent flat plate 71 can also have a touch panel function. As a touch panel, a touch panel of any type such as a resistive film type, an electrostatic capacitance type, an optical type, an ultrasonic type, etc. can be used.

[0129] The polarizing plate 3 provided on the surface of the image display panel 10 is bonded to the surface formed by the printed layer 76 of the front transparent plate 7 via the adhesive sheet 5. There is no particular restriction on the order of bonding, and the bonding of the adhesive sheet 5 on the image display panel 10 can be performed first, or the bonding of the adhesive sheet 5 on the front transparent plate 7 can be performed first. In addition, the bonding of the two can also be performed at the same time. From the viewpoint of the workability of bonding, it is preferred to peel off one release film (light release film) 2, bond the surface of the exposed adhesive sheet 5 to the image display panel 10, and then peel off another release film 1 (heavy release film), and bond the surface of the exposed adhesive sheet to the front transparent plate 7.

[0130] It is preferred to perform degassing after the adhesive sheet 5 and the front transparent plate 7 are attached, and the degassing is used to remove bubbles near the interface between the adhesive sheet 5 and the transparent flat plate 71 of the front transparent plate 7, the printed layer 76 and other non-flat parts. At this time, the adhesive sheet is before light curing, and the fluidity of the adhesive is high, so the adhesive can easily follow the shape of the non-flat part such as the height difference, and it is easy to remove bubbles. In addition, even after the adhesive sheet is stored for a long time under an environment such as a fluorescent lamp, the light curing of the adhesive sheet is suppressed, so the height difference absorption can be maintained.

[0131] As a degassing method, a suitable method such as heating, pressurization, and decompression can be used. For example, it is preferred to perform lamination while suppressing the mixing of bubbles under reduced pressure and heating, and then pressurize while heating by autoclaving or the like in order to suppress delayed bubbles. When degassing is performed by heating, the heating temperature is usually about 40°C to about 150°C. When pressurization is performed, the pressure is usually about 0.05MPa to about 2MPa.

[0132] After the adhesive sheet before photocuring is attached to an adherend such as a front transparent plate, the adhesive composition constituting the adhesive sheet is photocured. The amount of irradiation light during photocuring is not particularly limited as long as it is within the range that can photocuring the adhesive sheet. For example, the accumulated light amount is about 50 mJ / cm 2 ~about 10000mJ / cm2 .

[0133] By irradiation with light, the polymerization reaction of the photopolymerizable multifunctional compound proceeds, and the gel fraction of the adhesive sheet increases accordingly, thereby improving the adhesive reliability between the adhesive sheet 5 and the front transparent plate 7, and suppressing the generation of bubbles at the bonding interface when exposed to a high temperature environment for a long time. By adjusting the ultraviolet absorbency of the adhesive sheet and the type and amount of the photopolymerization initiator as described above, the photocuring reaction efficiency of the adhesive sheet can be maintained even when the light absorption band of the photopolymerization initiator overlaps with the light absorption wavelength of the ultraviolet absorber, so that an image display device with excellent adhesive reliability of the front transparent member can be formed.

[0134] [Optical film with adhesive]

[0135] like Figure 1 As shown in FIG. 1 , the adhesive sheet of the present invention can be used in the form of a film with an adhesive for fixing the adhesive sheet to an optical film or the like, in addition to the form in which release films are temporarily attached to both sides. Figure 3 In the embodiment shown, a release film 1 is temporarily attached to one surface of an adhesive sheet 5, and a polarizing plate 3 is fixed to the other surface of the adhesive sheet 5. Figure 4 In the illustrated embodiment, a pressure-sensitive adhesive sheet 4 is further provided on the polarizing plate 3 , and a release film 2 is temporarily attached to the pressure-sensitive adhesive sheet 4 .

[0136] In the case where an optical film such as a polarizing plate is previously bonded to the pressure-sensitive adhesive sheet, the release film 1 temporarily bonded to the surface of the pressure-sensitive adhesive sheet 5 is peeled off, and the pressure-sensitive adhesive sheet 5 is bonded to the front transparent member, and then the pressure-sensitive adhesive sheet 5 is photocured.

[0137] [Example]

[0138] Hereinafter, the present invention will be further described with reference to Examples, but the present invention is not limited to these Examples.

[0139] [Example 1]

[0140] (Preparation of base polymer)

[0141] 63 parts by weight of 2-ethylhexyl acrylate, 15 parts by weight of N-vinyl pyrrolidone (NVP), 13 parts by weight of hydroxyethyl acrylate and 9 parts by weight of methyl methacrylate as monomer components, 0.2 parts by weight of azobisisobutyronitrile as a thermal polymerization initiator and 233 parts by weight of ethyl acetate were put into a reaction vessel equipped with a thermometer, a stirrer, a condenser and a nitrogen inlet tube, and stirred for 1 hour in a nitrogen atmosphere at 23°C, and nitrogen replacement was performed. Then, the reaction was carried out at 65°C for 5 hours and then at 70°C for 2 hours, thereby preparing a solution of an acrylic base polymer with a weight average molecular weight of 450,000.

[0142] (Preparation of Adhesive Composition)

[0143] To the acrylic base polymer solution obtained above, 2 parts by weight of polypropylene glycol (#400) diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., “NK Ester APG-400”) as a multifunctional monomer, 0.16 parts by weight of trimethylolpropane adduct of xylylene diisocyanate (manufactured by Mitsui Chemicals, Inc., “Takenate D110N”) as an isocyanate crosslinking agent, 0.3 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., “KBM-403”), and 2,2-dimethoxy-1,2-diphenylethane-1-one (manufactured by BASF, “Irgacure 651”, absorption maximum wavelengths: 250 nm and 340 nm; extinction coefficient ε=1.7×10-6 at a wavelength of 380 nm) as a photopolymerization initiator were added with respect to 100 parts by weight of the base polymer. 2 [mL·g -1 cm -1 and 0.7 parts by weight of bis-ethylhexyloxyphenol methoxyphenyl triazine (manufactured by BASF, "Tinosorb S") as a UV absorber, and then uniformly mixed to prepare an adhesive composition.

[0144] (Manufacturing of adhesive sheets)

[0145] The above-mentioned adhesive composition was applied to the release-treated surface of a release film with a thickness of 75 μm (a polyester film with a silicone release treatment on the surface) in such a way that the thickness after drying would be 100 μm, and the solvent was removed by drying at 100°C for 3 minutes. Then, a release film with a thickness of 50 μm was laminated on the surface of the adhesive layer, and cross-linking was carried out by aging treatment for 3 days in an atmosphere of 25°C, thereby obtaining an adhesive sheet.

[0146] [Examples 2 to 6 and Comparative Examples 1 to 3]

[0147] In the preparation of the pressure-sensitive adhesive composition, the added amounts of the ultraviolet absorber and the photopolymerization initiator were changed as shown in Table 1. A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 1 except for the above.

[0148] [Examples 7 and 8]

[0149] In the preparation of the PSA composition, dipentaerythritol hexaacrylate (DPHA) was added as a polyfunctional monomer in the amount shown in Table 1 instead of polypropylene glycol diacrylate. A PSA sheet was obtained in the same manner as in Example 1 except for the above.

[0150] [evaluate]

[0151] <Light transmittance of adhesive sheet>

[0152] The release film on one side of the adhesive sheet was peeled off, the adhesive sheet was attached to an alkali-free glass plate, and then the release film on the other side was peeled off, and the transmission spectrum was measured using an ultraviolet-visible spectrophotometer (manufactured by Hitachi High-Technologies Corporation, "U-4100"). Based on the obtained spectrum, the transmittance of light at wavelengths of 365 nm, 380 nm, and 405 nm was read.

[0153] <Gel fraction of adhesive just after preparation>

[0154] About 0.2 g of adhesive was scraped from the adhesive sheet after 3 days of aging treatment and used as a sample for gel fraction determination. The sample was wrapped with a porous polytetrafluoroethylene membrane (manufactured by Nitto Denko Corporation, "NTF-1122") with a pore size of 0.2 μm cut into a size of 100 mm × 100 mm, and the wrapped opening was tied with a kite string. The weight of the sample was deducted from the total weight (A) of the porous polytetrafluoroethylene membrane and the kite string measured in advance to calculate the weight (B) of the adhesive sample. The adhesive sample wrapped with a porous polytetrafluoroethylene membrane was immersed in about 50 mL of ethyl acetate at 23°C for 7 days to dissolve the sol component of the adhesive outside the porous polytetrafluoroethylene membrane. After immersion, the adhesive wrapped with a porous polytetrafluoroethylene membrane was taken out, dried at 130°C for 2 hours, cooled naturally for about 20 minutes, and then the dry weight (C) was measured. The gel fraction of the adhesive was calculated according to the following formula.

[0155] Gel fraction (%) = 100 × (CA) / B

[0156] <Gel fraction of adhesive sheet after photocuring>

[0157] The energy density of UVA is 300mW / cm 2 The newly prepared adhesive sheet was irradiated with an ultraviolet lamp from the side where the release film was provided, with a cumulative light intensity of about 1000 mJ / cm 2 The adhesive was photocured by ultraviolet light. About 0.2 g of the adhesive was scraped from the photocured adhesive sheet and the gel fraction was measured in the same manner as above.

[0158] <Gel fraction after storage under fluorescent light>

[0159] The PSA sheet with release films on both sides was left at a distance of 1.5 m from a fluorescent lamp (FLR32S·N / NX manufactured by Panasonic Corporation; color temperature 5000K) for 7 days, and then about 0.2 g of the PSA was scraped off and the gel fraction was measured in the same manner as above.

[0160] <Absorption of height difference>

[0161] The adhesive sheet stored under a fluorescent lamp for 1 week was cut into a size of 75 mm × 45 mm, and the release film on one side was peeled off from the adhesive sheet, and it was bonded to the center of a polarizing plate (100 mm × 50 mm) by a roll laminator (pressure between rollers: 0.2 MPa, feed speed: 100 mm / min), and the polarizing plate was obtained by bonding a triacetyl cellulose film with a thickness of 40 μm on both sides of a polyvinyl alcohol polarizer. Then, the release film on the other side of the adhesive sheet was peeled off, and it was bonded to a glass plate (100 mm × 50 mm) with a thickness of 500 μm and a black ink with a thickness of 20 μm printed in a frame shape on the periphery using a roll laminator (pressure between rollers: 0.2 MPa, feed speed: 100 mm / min). The ink printing area of ​​the glass plate is 5 mm from both ends in the short side direction and 15 mm from both ends in the long side direction, and the black ink layer is in contact with the area of ​​5 mm from the ends of the four sides of the adhesive sheet. The sample was treated in an autoclave (50°C, 0.5 MPa) for 30 minutes and then observed using a 20x digital microscope to confirm the presence or absence of bubbles near the boundary of the printed area of ​​the black ink. Samples with no bubbles were evaluated as OK, and samples with bubbles were evaluated as NG.

[0162] <Adhesion reliability after light curing>

[0163] Using the adhesive sheet just prepared, a sample was prepared in the same manner as the above-mentioned height difference absorption evaluation, in which a polarizing plate was bonded to one surface of the adhesive sheet and a glass plate with black ink printed in a frame shape on the periphery was bonded to the other surface. The energy density of the UVA was 300 mW / cm 2 The sample was irradiated with an ultraviolet lamp from the glass plate side with a cumulative light intensity of about 1000 mJ / cm 2 The adhesive was cured by ultraviolet light, and then placed in an oven at 85°C for 72 hours. The samples taken out of the oven were checked for the presence of bubbles by the same method as the height difference absorption test. Samples with no bubbles were evaluated as OK, and samples with bubbles were evaluated as NG.

[0164] Table 1 shows the compositions of the adhesives of Examples and Comparative Examples (type and amount of multifunctional monomer, amount of ultraviolet absorber and photopolymerization initiator), light transmittance of the adhesive sheets, gel fraction, and evaluation results of step absorption and adhesion reliability.

[0165]

[0166] The gel fraction of the adhesive sheets of Examples 1 to 7 after standing for 7 days under fluorescent light changed little, and when irradiated with 1000 mJ / cm 2The gel fraction of the adhesive sheets of Comparative Examples 1 and 2 increased significantly after being left under a fluorescent lamp for 7 days, and the height difference absorption decreased.

[0167] In Comparative Example 2, the amount of ultraviolet absorber added was small, and the transmittance of the adhesive sheet at wavelengths of 380 nm and 365 nm was large, so it is considered that photocuring under the storage environment occurred. The amount of ultraviolet absorber added was the same in Examples 1 and 2 and Comparative Example 1, but photocuring under the storage environment occurred in Comparative Example 1 in which the amount of photopolymerization initiator added was large. From these results, it can be seen that in order to suppress photocuring under the storage environment, it is important not only to add the ultraviolet absorber but also to adjust the amount of photopolymerization initiator added.

[0168] In Comparative Example 3, in which 1.0 part by weight of an ultraviolet absorber was added, photocuring under a fluorescent lamp was suppressed, but even when irradiated with 1000 mJ / cm 2 The ultraviolet rays of the present invention are not enough to increase the gel fraction, and the adhesive reliability is poor. In Comparative Example 3, it is believed that the absorption of the excitation light generated by the ultraviolet absorber is large, and the amount of light absorbed by the photopolymerization initiator is small, so the photocuring efficiency is reduced.

[0169] The above results show that it is possible to achieve both storage stability and photocuring efficiency by adding an ultraviolet absorber to a photocurable adhesive sheet to adjust the absorption characteristics and adjusting the type (absorption wavelength) and addition amount of the photopolymerization initiator.

Claims

1. An adhesive sheet, which is a photocurable adhesive sheet obtained by forming an adhesive composition into a layer, the adhesive composition comprising: a base polymer having a crosslinked structure, a photopolymerizable multifunctional compound having two or more photopolymerizable functional groups in one molecule, a photopolymerization initiator and an ultraviolet absorber, wherein: The transmittance of the adhesive sheet for light with a wavelength of 420 nm is 85% or more, the transmittance for light with a wavelength of 405 nm is 80% or more, and the transmittance for light with a wavelength of 380 nm is 4% to 25%. When the content of the photopolymerization initiator relative to 100 parts by weight of the base polymer is w parts by weight, the extinction coefficient of the photopolymerization initiator at a wavelength of 380 nm is ε (mL·g -1 cm -1 ), the product of ε and w εw is 10~100.

2. The adhesive sheet according to claim 1, wherein The adhesive sheet has a transmittance of 1% or less at a wavelength of 365 nm.

3. The adhesive sheet according to claim 1 or 2, wherein The extinction coefficient of the photopolymerization initiator at a wavelength of 405 nm is 50 mL·g -1 cm -1 The extinction coefficient ε at a wavelength of 380 nm is 80 mL·g -1 cm -1 above.

4. The adhesive sheet according to claim 1 or 2, wherein The photopolymerization initiator has an absorption maximum in the wavelength range of 310 nm to 370 nm.

5. The adhesive sheet according to claim 1 or 2, wherein The content w of the photopolymerization initiator is 0.05 to 1 part by weight relative to 100 parts by weight of the base polymer.

6. The adhesive sheet according to claim 1 or 2, wherein When the transmittance of the adhesive sheet at a wavelength of 380 nm is defined as T%, εwT is 100~1200.

7. The adhesive sheet according to claim 1 or 2, wherein The ultraviolet absorber includes one or more selected from the group consisting of triazine compounds and benzotriazole compounds.

8. The adhesive sheet according to claim 1 or 2, wherein The pressure-sensitive adhesive sheet contains an acrylic polymer as the base polymer.

9. The adhesive sheet according to claim 1 or 2, wherein The base polymer contains a hydroxyl group-containing monomer as a monomer unit, and forms a crosslinked structure by bonding with the hydroxyl group via an isocyanate crosslinking agent.

10. The adhesive sheet according to claim 1 or 2, wherein The photopolymerizable multifunctional compound is a multifunctional (meth)acrylate.

11. The adhesive sheet according to claim 1 or 2, wherein The pressure-sensitive adhesive sheet contains 0.3 to 10 parts by weight of the photopolymerizable multifunctional compound based on 100 parts by weight of the base polymer.

12. The adhesive sheet according to claim 1 or 2, wherein The adhesive sheet has a gel fraction of 30% to 80%.

13. The adhesive sheet according to claim 1 or 2, wherein The adhesive sheet was irradiated with 1000 mJ / cm 2 The gel fraction after light curing is more than 5% higher than that before light curing due to ultraviolet rays.

14. An optical film with an adhesive, wherein: The optical film with adhesive comprises: an optical film; a first adhesive sheet laminated on a first main surface of the optical film; and a second adhesive sheet laminated on a second main surface of the optical film, and The first pressure-sensitive adhesive sheet is the pressure-sensitive adhesive sheet according to any one of claims 1 to 13.

15. A method for manufacturing an image display device, which is a method for manufacturing an image display device having a transparent member having a height difference portion arranged on a visible side surface, wherein: The adhesive sheet according to any one of claims 1 to 13 is bonded to the transparent member, and then the adhesive sheet is irradiated with active light rays, thereby photocuring the adhesive composition of the adhesive sheet.